Ionic and Electronic Conduction in TiNb2O7 - Griffith, Kent J; Seymour, Ieuan D; Hope, Michael A; Butala, Megan M; Lamontagne, Leo K; Preefer, Molleigh B; Koçer, Can P; Henkelman, Graeme; Morris, Andrew J; Cliffe, Matthew J; Dutton, Siân E; Grey, Clare P (Journal of the American Chemical Society, 2019)
TiNb2O7 is a Wadsley–Roth phase with a crystallographic shear structure and is a promising candidate for high-rate lithium ion energy storage. The fundamental aspects of the lithium insertion mechanism and conduction in TiNb2O7, however, are not well-characterized. Herein, experimental and computational insights are combined to understand the inherent properties of bulk TiNb2O7. The results show an increase in electronic conductivity of seven orders of magnitude upon lithiation and indicate that electrons exhibit both localized and delocalized character, with a maximum Curie constant and Li NMR paramagnetic shift near a composition of Li0.60TiNb2O7. Square-planar or distorted-five-coordinate lithium sites are calculated to invert between thermodynamic minima or transition states. Lithium diffusion in the single-redox region (i.e., x ≤ 3 in Li x TiNb2O7) is rapid with low activation barriers from NMR and D Li = 10–11 m2 s–1 at the temperature of the observed T 1 minima of 525–650 K for x ≥ 0.75. DFT calculations predict that ionic diffusion, like electronic conduction, is anisotropic with activation barriers for lithium hopping of 100–200 meV down the tunnels but ca. 700–1000 meV across the blocks. Lithium mobility is hindered in the multiredox region (i.e., x > 3 in Li x TiNb2O7), related to a transition from interstitial-mediated to vacancy-mediated diffusion. Overall, lithium insertion leads to effective n-type self-doping of TiNb2O7 and high-rate conduction, while ionic motion is eventually hindered at high lithiation. Transition-state searching with beyond Li chemistries (Na+, K+, Mg2+) in TiNb2O7 reveals high diffusion barriers of 1–3 eV, indicating that this structure is specifically suited to Li+ mobility.